Determination of the dynamic characteristics of freight wagons with various bogie - Myamlin, Sergey; Lingaitis, Leonas P.; Dailydka, Stasys; Vaičiūnas, Gediminas; Bogdevičius, Marijonas; Bureika, Gintautas (Transport, 2015)
In most cases, dynamic characteristics determine the wagon maintenance cycle, traffic safety, reliability and durability performance. The main dynamic indicators include the vertical Kvd and horizontal Khd dynamic coefficients as well as the stability coefficient Ks, which determines the wheel flange resistance to derailment. The article compares dynamic indications for three different types of bogies. There were no tangible differences observed for all the three different types of bogies running at a speed of 40 to 120 km/h on a direct tangent rail section. Nevertheless, there is a realistic potential to improve the dynamic indicators of a freight wagon by rationalising suspension unit parameters.First Published Online: 27 Mar 2015